PENGARUH VOLUME LALU LINTAS TERHADAP TINGKAT KEBISINGAN PADA JALAN BUNG TOMO SAMARINDA SEBERANG - ZULKIPLI, SELAMAT (KURVA S JURNAL MAHASISWA, 2014)
This research stems from the observation volume of traffic in Samarinda Seberang Jalan Bung Tomogrowing dense population and the schools are close to the highway, which serve as the object of research, it iscertainly affect the traffic volume, vehicle speed and the noise that occurs.This study aimed to analyze the level of noise due to vehicle traffic on the road Bung Tomo SamarindaSeberang, create a mathematical model expressing the relation between the level of noise with the volume ofvehicles and analyze equivalence vehicle due to traffic noise. Data analysis using multiple linear regression inSPSS 16.0 for Windows. The data resulting from the analysis include: Value Correlation (correlation) betweenthe independent variables and the dependent variable, level of significance (significance) of each regressioncoefficient, Model Noise Level, Test Data normalcy and the coefficient of determination.Based on the analysis, the highest level of noise of vehicles on the road Bung Tomo Samarinda Seberangamounted to 86.2 dBA. The model best level of traffic noise is noise (Y) = 72.449 - 0,86Volmc + 015Volmc +160Volhv - 023V with R2 = 0,862 X1 is the volume where the value of the motorcycle, light vehicle volume X2and X3 volume of heavy vehicles. Noise equivalent value of each vehicle is for motorcycles: 1.9; light vehicles:1 and heavy vehicles: 0.12. Average speed of 36.38 km / h